Prostaglandin E2 Dilates Intracerebral Arterioles When Applied to Capillaries: Implications for Small Vessel Diseases - Rosehart, Amanda C.; Longden, Thomas A.; Weir, Nick; Fontaine, Jackson T.; Joutel, Anne; Dabertrand, Fabrice (Frontiers in Aging Neuroscience, 2021)
Prostaglandin E2 (PGE2) has been widely proposed to mediate neurovascular coupling by dilating brain parenchymal arterioles through activation of prostanoid EP4 receptors. However, our previous report that direct application of PGE2 induces an EP1-mediated constriction strongly argues against its direct action on arterioles during neurovascular coupling, the mechanisms sustaining functional hyperemia. Recent advances have highlighted the role of capillaries in sensing neuronal activity and propagating vasodilatory signals to the upstream penetrating parenchymal arteriole. Here, we examined the effect of capillary stimulation with PGE2 on upstream arteriolar diameter using an ex vivo capillary-parenchymal arteriole preparation and in vivo cerebral blood flow measurements with two-photon laser-scanning microscopy. We found that PGE2 caused upstream arteriolar dilation when applied onto capillaries with an EC50 of 70 nM. The response was inhibited by EP1 receptor antagonist and was greatly reduced, but not abolished, by blocking the strong inward-rectifier K+ channel. We further observed a blunted dilatory response to capillary stimulation with PGE2 in a genetic mouse model of cerebral small vessel disease with impaired functional hyperemia. This evidence casts previous findings in a different light, indicating that capillaries are the locus of PGE2 action to induce upstream arteriolar dilation in the control of brain blood flow, thereby providing a paradigm-shifting view that nonetheless remains coherent with the broad contours of a substantial body of existing literature.